KUALITAS PELAYANAN E-AUCTION PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG SURAKARTA - Dwi Nugroho (Master of Public Administration, Universitas Slamet Riyadi, 2018)
Wealth Of State And An Auction Of Surakarta”. Slamet Riyadi University.Thesis, unpublished.The purpose of this study is: to know the procedure of service andcommunity satisfaction in E-Auction at the Service Office a wealth of Stateand an auction of Surakarta? Research conducted at the Service Office awealth of State and an auction. Research conducted using qualitativeapproach. Data collection techniques used are in-depth interviews,documentation, and observation/observation. Data analysis techniquesusing interactive analysis models. Results of the study shows that theprocedure's E-auction services On Service Office a wealth of State andSurakarta Auction consists of 11 stages, all stages conducted meleluiinternet media, the level of satisfaction of the public against the E-Auction,belongs to the satisfied, because the expectations of society.Keywords: quality of service and E-Auction.